2011
DOI: 10.1111/j.1476-5381.2011.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of innovative small molecule drugs used for cancer therapy with drug transporters

Abstract: Multiple new small molecules such as tyrosine kinase, mammalian target of rapamycin (mTOR) and proteasome inhibitors have been approved in the last decade and are a considerable progress for cancer therapy. Drug transporters are important determinants of drug concentrations in the systemic circulation. Moreover, expression of drug transporters in blood-tissue barriers (e.g. blood-brain barrier) can limit access of small molecules to the tumour (e.g. brain tumour). Finally, transporter expression and (up)regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 111 publications
(251 reference statements)
0
28
0
Order By: Relevance
“…For example, axitinib (7) and imatinib (8) were previously identified as substrates of OATP1B1 and OATP1B3, respectively, and a number of other TKIs, including lapatinib (9), pazopanib (10), and vandetanib (Caprelsa package insert; see: www.astrazeneca-us.com), were recently demonstrated to potently inhibit the function of OATP1B1 and/or OATP1B3 using in vitro model systems. However, a systematic approach to evaluate the ability of TKIs to interact with OATP1B-type transporters and subsequently affect drug disposition profiles is still lacking (11). The aims of the current study were to ( i ) evaluate transport of 10 different TKIs by OATP1B-type transporters in vitro ; ( ii ) determine the pharmacokinetics of a lead TKI substrate, sorafenib, in mice that are knock-out for the ortholog transporter Oatp1b2; and ( iii ) assess the degree of functional restoration in mice that are knock-in for either OATP1B1 or OATP1B3.…”
Section: Introductionmentioning
confidence: 99%
“…For example, axitinib (7) and imatinib (8) were previously identified as substrates of OATP1B1 and OATP1B3, respectively, and a number of other TKIs, including lapatinib (9), pazopanib (10), and vandetanib (Caprelsa package insert; see: www.astrazeneca-us.com), were recently demonstrated to potently inhibit the function of OATP1B1 and/or OATP1B3 using in vitro model systems. However, a systematic approach to evaluate the ability of TKIs to interact with OATP1B-type transporters and subsequently affect drug disposition profiles is still lacking (11). The aims of the current study were to ( i ) evaluate transport of 10 different TKIs by OATP1B-type transporters in vitro ; ( ii ) determine the pharmacokinetics of a lead TKI substrate, sorafenib, in mice that are knock-out for the ortholog transporter Oatp1b2; and ( iii ) assess the degree of functional restoration in mice that are knock-in for either OATP1B1 or OATP1B3.…”
Section: Introductionmentioning
confidence: 99%
“…BCRP. In vitro studies identified multiple drugs, such as statins (e.g., atorvastatin), anti-infective drugs, and antineoplastic agents (e.g., mitoxantrone, topotecan, gefitinib, imatinib), as substrates of BCRP (Poguntke et al, 2010;Meyer zu Schwabedissen and Kroemer, 2011;Mandery et al, 2012). Studies in Bcrp-deficient mice showed a major effect of Bcrp on plasma concentrations of sulfasalazine and topotecan (Jonker et al, 2000;Zaher et al, 2006).…”
mentioning
confidence: 99%
“…However, premeiotic (e.g., spermatogonia, early spermatocytes) and postmeiotic (e.g., late primary and secondary spermatocytes, spermatids and sperm) germ cells are also equipped with efflux pump transporters to actively pump harmful, but also therapeutic, drugs and substances out of the adluminal compartment. 1,9,13 At present, ∌800 drug transporters are known to date found in different epithelial/endothelial cells including cancer cells; 14-16 as well as Sertoli cells and almost all classes of germ cells in the testis. 1,9,17 Unfortunately, virtually all the reports found in the literature regarding the study of drug transporters in the testis were limited to cellular distribution/localization studies, investigating the cellular expression of different drug transporters in the testis without any pertinent functional studies in particular the transport of drugs across the BTB.…”
Section: Drug Transporters and Blood-testis Barrie R (Btb) Dynamicsmentioning
confidence: 99%